Combined UV/Fenton and SBR treatment of a semi-aerobic landfill leachate - Gan, Chin Heng; Emad Soliman Elmolla; Malay Chaudhuri (Universiti Kebangsaan Malaysia, 2013)
This study examined the combined UV/Fenton and sequencing batch biological reactor (SBR) treatment of a semi-aerobic landfill leachate. Fenton pretreatment of the leachate was optimized by the response surface methodology (RSM). UV/Fenton pretreatment of the leachate was performed under the optimum operating conditions of the Fenton pretreatment (H2O2/COD molar ratio 2.25, H2O2/Fe2+ molar ratio 10.0 and reaction/irradiation time 1.5 h). The characteristics of the UV/Fenton pretreated leachate were: COD 390 mg/L, sCOD 330 mg/L, BOD5 136 mg/L, BOD5/COD ratio 0.35, NH3-N 112 mg/L, TKN 157 mg/L,NO3--N 6.8 mg/L and colour 99 Pt-Co Unit. SBR treatment of the UV/Fenton pretreated leachate resulted in sCOD, BOD5 and NH3-N removal of 78%, 81% and 88%, respectively. The final effluent characteristics were: COD 92 mg/L, sCOD 71 mg/L, BOD5 26 mg/L, NH3-N 7 mg/L, NO3--N 27 mg/L, TKN 13 mg/L and TSS 38 mg/L. The effluent met the Malaysian discharge standard (B) – COD 100 mg/L, BOD5 50 mg/L and TSS 100 mg/L. Combined UV/Fenton and SBR is an effective treatment for mature leachate from semi-aerobic landfill.